Directions for eco-innovation funding in Poland – outlook for 2014-2020 - Osuch-Rak, Ewa; Proczek, Magdalena (Studia Ecologiae et Bioethicae, 2014)
Eco-innovation is a new paradigm of development in the European Union. This is the key to resolving issues related to environmental pollution while contributing to the competitiveness of the European economy. The role of eco-innovation will grow in the future. This study attempts to examine Polish preparations for the implementation of the European Union's "Europe 2020 strategy" and integrated strategies, with an emphasis on the implementation of the objectives related to eco-innovation. At the same time, the article touches on the issues of a national system for supporting eco-innovation and the role of eco-innovation in both EU and Polish public policy.